The Rules of Balinese Nasalization - I Made Suwendi (Dwijendra University, 2021)
Balinese has a stratified system called anggah-ungguhing basa Bali. The existence of this system is distinguished it from Indonesian and / or the other regional languages in Indonesia. In addition, Balinese has two major dialects, namely the Bali Aga dialect and the Bali Dataran dialect. The Bali Aga dialect does not recognize the language level system, on the contrary, in the Bali Dataran dialect this system greatly influences the use of Balinese language itself. The difference in this system was also reflected in its morphological system, especially in forming the words with nasal prefix. It was interesting to be observed. In relation with that, this writing focused on the Balinese nasalization system. The purpose of this research was to find out the rules of Balinese nasalization. The data in this study were collected by using literature study and observation methods. Then, the data were analyzed using descriptive analysis methods. The theory used in investigating this problem was morphology theory. After analyzing the data that had been collected, it was found that the nasal prefix N- in Balinese which was affixed to the original form or the basic form which was preceded by certain phonemes, that had already changed form. The form of this changing was called an allomorph. Thus the allomorphs found from the merging of the nasal prefixes were: n- n-, m- m-, ng- ŋ-., And ny- ñ-.